(untitled) (Research, Society and Development, 2021)
Ergonomics plays a role of great relevance in the work environment, covering the relationship between man and the various technologies present in these environments. Dimensions such as height and width of work surfaces, limits of equipment reach should be considered, relating them to the activities of health professionals. The present study aimed to identify the most frequent ergonomic risks to which health professionals of the Neonatal Intensive Care Unit (NICU) are exposed. The research was carried out in a reference public maternity hospital in the state of Piauí. The sample consisted of 70 volunteer employees. The inclusion criteria were employees between 30 and 50 years, of both sexes, who had been in at least 1 year performing the current function within the company. For data collection, a questionnaire on ergonomics was elaborated, applied individually. Then, the ergonomic evaluation of the NICU was performed, through photographic records of the environment and equipment, using as reference the regulatory standards related to ergonomics. Finally, the collected data were organized into microsoft office excel 2013 spreadsheets and exported to the SPSS 22.0 program. The results showed that the environment constitutes incompatibility with the physical-environmental results determined by the regulatory standards, presenting organizational design failures, lighting, temperature and noise. Thus, the inadequacies were explained, pointing out the necessary requirements for the improvement of the sector and its compliance with compatibility standards in relation to the analyzed aspects, so that it based measures for environmental adequacy.